Sensorless motor drive for brushless DC motors - Tanchuco, Jesus A. III (2011)
This project developed a design for a sensorless brushless DC motor drive for motors to be used for electric vehicles. Sensing of the rotor position is achieved despite the absence of hall effect sensors. This was done using the back-EMF generated by the unenergized phase. The speed, direction and other inputs and outputs were controlled using a Z8FMC16100 microcontroller, producing six Pulse Width Modulation (PWM) outputs that are 120 degrees apart. Also included is a cycle-by-cycle current-limiting in order to prevent a current overshoot during startup. The project was used to drive a 48V 500W Brushless spoke motor. This motor was mounted to a bicycle with training wheels to remove the need of the user to balance the vehicle.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Brushless direct current electric motors -- Design and construction; Electric motors